Ecology and the Fantastic. The Example of "Le monde enfin" by Jean-Pierre Andrevon - Katarzyna Gadomska (Universitat Autònoma de Barcelona, 2020)
This article analyzes Le monde enfin by the French writer Jean-Pierre Andrevon as an example of the relation between the new fantastic and ecology. Adopting canonical fantastic theories as a point of reference, it presents the development of the new fantastic as a genre and Andrevon’s important place in this literary field. Thereafter, it examines the narrative roles of humans and nature in Le Monde enfin in order to demonstrate how the author plays with the conventional definitions of the character and the malevolent phenomenon. As the study strives to prove, Andrevon’s ecological preoccupations strongly influence his literary work. Moreover, the article evokes intertextual references in Le Monde enfin and examines the text in relation to philosophical concepts such as deep ecology and the Gaia hypothesis.